Employment law stories - Estreicher, Samuel; Lester, Gillian; Estlund, Cynthia (Foundation Press, 2007)
"Employment law is emerging as an important practice area. This title provides behind-the-scenes descriptions of the landmark cases-the litigants, the lawyers, the strategy-that helped shape this growing field. This account of emerging law is designed to help the student understand that, well before appellate judges are involved, the basic narrative and the doctrinal and policy potential of the case have been set by the decisions of litigants and their representatives. Several chapters are also devoted to the story behind some of the principal statutes in the area."--Publisher's website
Keywords: Labor laws and legislation / United States / Cases; Discrimination in employment / United States / Cases; Discrimination in employment; Labor laws and legislation; United States; USA